Propaganda by Deed and the Destruction of Authority in Ahlam Alnisa' Alharem: An Goldman's Anarcho-Feminist Reading - Rendi Muhammad Fauzi; Rohanda Rohanda; Khomisah Khomisah (Mahesa Research Center, 2026)
This study examines the forms of women's resistance against patriarchal structures in Fatima Mernissi's novel, Ahlam Alnisa' Alharem. In contrast to previous liberal feminist approaches that generally emphasize negotiation and systemic reform, this research employs Emma Goldman's Anarcho-Feminist perspective to analyze direct and confrontational resistance strategies. Utilizing a descriptive-analytical qualitative method, the present study draws upon two primary concepts: Propaganda by Deed and The Destruction of Authority. The findings indicate that the female characters within the Harem articulate their autonomy through direct action, the assertion of bodily rights, and civil disobedience, rather than mere compliance. Furthermore, these acts aim to deconstruct three intersecting forms of authority conceptually referred to as the